Holt-based activity patterns of smooth-coated otter (Lutrogale perspicillata) in the Lower Kinabatangan Wildlife Santuary, Sabah, Malaysia - Leona Wai; Meaghan N. Evans; Henry Bernard; Benoit Goossens (©IUCN/SCC Otter Specialist Group, 2019)
Despite being one of the most biodiverse regions in the world, not much is known concerning the ecology of the otters on Borneo. We conducted a study to document the activity patterns of the smooth-coated otter, Lutrogale perspicillata, in increasingly disturbed and fragmented habitats in the Lower Kinabatangan Wildlife Sanctuary (LKWS), located in the Malaysian state of Sabah, northern Borneo. The aim was to gather ecological information for establishing baseline data and to understand better the otter behavior in this region of Sabah. We deployed camera traps at active otter holts, grooming and sprainting sites for 15 non-consecutive months and utilized the photographs to model the activity patterns of the otter using kernel’s density estimate modeling. Results showed that L. perspicillata in the LKWS was mainly crepuscular, with otter activity mainly occurring during early morning (0600 h) and late afternoon (1600 h - 1800 h). Grooming activity peaked at 0600 h while sprainting activity peaked at both 0800 h and 1700 h. We suggest that activity patterns of L. perspicillata may be influenced by prey availability, human disturbance and environmental temperature.